Biodegradation of an antimicrobial compound triclosan under sulfate reducing condition - Boopathy, Raj; Cortez, Jacob (Universitas Nahdlatul Ulama Surabaya, 2022)
Triclosan is an antibacterial and antifungal agent that is present in many detergents and surgical cleaning treatment products. This antimicrobial compound is discharged from households and collected at the local sewage treatment plant. Because triclosan inhibits phospholipid biosynthesis, it affects the microbial population that perform waste degradation. Sewage treatment plants are the major reservoir of triclosan as the wastewater from various households are discharged and treated in the local sewage treatment plant. This study was conducted to determine whether triclosan degradation occurs in the anaerobic digester of the Thibodaux Sewage Treatment Plant. Bacterial enrichment cultures were developed under various electron acceptor conditions including nitrate-reducing, sulfate-reducing, and mixed electron acceptor condition. The results showed the bacterial consortia developed under various conditions were not inhibited by 100 ppm of triclosan. More than 96% of triclosan was removed in both co-metabolic and triclosan as the sole carbon source conditions under sulfate-reducing condition. The molecular analysis of the consortium showed wide biodiversity of bacteria in the consortium.